Expression of a novel gene encoding protease inhibitor from metagenome of sponge in Vietnam - Hong, Tran Thi; Dat, Ton That Huu; Hoa, Nguyen Phuong; Cuong, Pham Viet; Cuc, Nguyen Thi Kim (Academia Journal of Biology, 2019)
Marine sponge is known as a “gold mine” of natural products from marine environment. Many novel bioactive compounds have been isolated from marine sponges and sponge-associated microorganisms such as antibiotics, anti-cancer compounds, protease inhibitors, etc. In this study, we selected a gene encoding protease inhibitor from metagenome of a sponge collected in Da Nang to express in Escherichia coli BL21(DE3). The gene PI-DN9 encoding protease inhibitor (1.3 kb) was cut off cloning vector pUC57/PI-DN9 containing gene PI-DN9 and inserted into expression vector pET32a(+), the recombinant vector pET32a(+)/PI-DN9 then was transformed and expressed in the E. coli strain BL21(DE3). Results showed that recombinant protein (50 kDa) was expressed successfully at 25°C, 1 mM of IPTG in 5 hours. The recombinant protein was purified using Ni-NTA affinity chromatography column. Western blot assay and bioactive assay showed good activity of the purified protein.